Survey of musculoskeletal pain among dental clinician in Kulliyyah of Dentistry IIUM - Sukmasari, Susi; Ismail, Ahmad Faisal; Hamshah, Arbaatul Arroshikin Nazirah (2016)
Introduction: Inflammatory and degenerative conditions that affect the muscles, ligaments, joints and peripheral nerves are known as musculoskeletal disorders (MSDs). Dental personnel have an increased risk of developing musculoskeletal disorders because of long working duration and involvement of repetitive movement. This study aimed to determine the prevalent site of musculoskeletal pain and to identify its associated risk factors among dental clinician in Kulliyyah of Dentistry IIUM. Methodology: A validated, pilot-tested self-administered questionnaires were distributed to 160 dental clinicians between March and June 2014 using convenience sampling method. Inclusion criteria include dentist, clinical supervisors or clinical dental students. Exclusion criteria includes dental clinician whom were diagnosed with musculoskeletal disorders. Data were recorded and analyzed using statistical package for the social science (SPSS) software version 21. Pearson correlation test was used to determine the association between the risk factors and pain sites. Result: A total of 146 participants completed the questionnaire (91.3% response rate). The sample consist of 40 dentist (27.4%), 36 Year 3 student (24.7%) and 35 participants (24%) respectively from Year 4 and Year 5. There was high prevalence of neck pain (79.5%), back shoulder pain (74.7%) and lower back pain (71.9%) among dental clinician. Significant correlation was found between physical activities with upper body region pain sites (r = 0.170, p=0.042) and lower body region pain sites(r = 0.221, p=0.008).There were significant association between repetitive movements and wrist bending with upper and lower body region pain sites(r = 0.320, p = <0.001) (r = 0.278, p =0.001). No correlation between awkward postures with upper and lower body pain sites. Conclusions: The most prevalent site of musculoskeletal pain experienced by dental clinician was neck and the least was left arm. Repetitive movements, wrist bending and physical activities were associated with upper and lower body region pain sites.